Nanoencapsulation of Zataria multiflora Essential Oil Containing Linalool Reduced Antibiofilm Resistance against Multidrug-resistant Clinical Strains - Mohamadi, Neda; Adeli-Sardou, Mahboubeh; Ansari, Mehdi; Pakdel, Atousa; Kosar, Muberra; Sharififar, Fariba (Bentham Science Publ Ltd, 2025)
Background The rise in antimicrobial resistance, caused by the production of biofilms by bacteria, is a significant concern in the field of healthcare. Nanoemulsion technology presents itself as a viable alternative in the quest to circumvent antibiotic resistance in pathogenic bacteria. Objective The aim of this research was to form a sustainable nanoemulsion from Z. multiflora, and evaluate its antibacterial and anti-biofilm activities against the clinical isolates of Pseudomonas aeruginosa, Proteus mirabilis, and Staphylococcus aureus. Materials and Methods Bioactive compounds of the oil were identified using GC-MS. Zataria multiflora essential oil (ZMEO) nanoemulsion was formulated as a water-dispersible nanoemulsion with a diameter of 184.88 +/- 1.18 nm. The antibacterial and antibiofilm activities of the essential oil in both pure and nanoemulsion forms were assessed against pathogenic bacteria causing hospital-acquired infections using minimal inhibitory concentrations (MICs) and the microtiter method, respectively. Results The main constituents were found to be linalool (78.66%), carvacrol (14.25%), and alpha-pinene (4.53%). Neither ZMEO nor the emulsified ZMEO showed any antimicrobial activity. However, ZMEO exhibited a low inhibition of biofilm formation by P. mirabilis, S. aureus, and P. aeruginosa. The most promising finding was that when the emulsified ZMEO was present at a concentration of 750 mu g/mL, it significantly reduced biofilm formation by the aforementioned bacteria to 39.68% +/- 2.62, 56.54% +/- 3.35, and 59.60% +/- 2.88, respectively. This result suggests that ZMEO nanoemulsion has the potential to effectively disrupt persistent biofilms and enhance the penetration of antimicrobial agents into the biofilm matrix. Conclusion In conclusion, the study provides evidence supporting the use of ZMEO nanoemulsion as a potential treatment option for combating biofilm-related infections caused by Pseudomonas aeruginosa, Proteus mirabilis, and Staphylococcus aureus. Further research is warranted to explore the practical application of the proposed essential oil in clinical settings.
Keywords: Zataria multiflora; essential oil; nanoemulsion; biofilm formation; GC-MS; antimicrobial resistance